Update on calcitonin screening for medullary thyroid carcinoma and the results of a retrospective analysis of 12,984 patients with thyroid nodules - Bröcker, Martina; Simon, Dietmar; Fries, Mirka; Kornely, Elisabeth; Weber, Manuel; Vardarli, Irfan; Gilman, Elena; Herrmann, Ken; Görges, Rainer (Cancers, 2023)
Background: We provide an update on calcitonin (Ctn) screening for the early detection of medullary thyroid carcinoma (MTC) and present the results of a large single-center analysis evaluating sex-specific cut-off-levels and long-term courses. Methods: A total of 12,984 consecutive adult patients (20.1% male and 79.9% female) with thyroid nodules who had undergone routine Ctn measurement were retrospectively analyzed. Patients with confirmed suspicious Ctn values were referred for surgery. Results: Ctn measurements were elevated in 207 (1.6%) patients, with values below twice the sex-specific reference limit in 82% of these cases. Further clarification was possible in 124/207 cases, of which MTC could be ruled out in 108 cases. Histopathological assessment confirmed MTC in 16/12,984 patients. Conclusions: Our extrapolated MTC prevalence of 0.14% is significantly lower than that described in early international screening studies. The stimulation test can usually be dispensable when using a decision-making concept based on sex-specific basal Ctn cut-off values. Ctn screening is recommended even in patients with very small thyroid nodules. High quality standards in pre-analytics, laboratory measurements, and the interpretation of data must be ensured, as well as close interdisciplinary cooperation between medical disciplines.